2014
DOI: 10.1063/1.4863175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulse polarity on nanosecond pulse driven dielectric barrier discharge plasma actuators

Abstract: Articles you may be interested inCapacitances and energy deposition curve of nanosecond pulse surface dielectric barrier discharge plasma actuator Rev. Sci. Instrum. 85, 053501 (2014); 10.1063/1.4871552 Competition between pressure effects and airflow influence for the performance of plasma actuators Phys. Plasmas 21, 053511 (2014); 10.1063/1.4880098Dielectric material degradation monitoring of dielectric barrier discharge plasma actuators Nanosecond pulse driven dielectric barrier discharge plasma actuators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…This topology is composed of a straight region at the top of an hemispheric region, this latter region being centered at the edge of the active electrode. This is typical of the pressure wave produced by a nanosecond DBD as already described in literature [8,12,16,23,26,28]. All of these publications suggest that the semispherical part of the wave is caused by the contribution of the fast energy released at the tip of the active electrode whereas the linear signature is directly correlated with the plasma propagation along the dielectric surface.…”
Section: C) Electrical Energy Consumption Of the Actuatormentioning
confidence: 87%
See 1 more Smart Citation
“…This topology is composed of a straight region at the top of an hemispheric region, this latter region being centered at the edge of the active electrode. This is typical of the pressure wave produced by a nanosecond DBD as already described in literature [8,12,16,23,26,28]. All of these publications suggest that the semispherical part of the wave is caused by the contribution of the fast energy released at the tip of the active electrode whereas the linear signature is directly correlated with the plasma propagation along the dielectric surface.…”
Section: C) Electrical Energy Consumption Of the Actuatormentioning
confidence: 87%
“…Good effectiveness has been demonstrated more specifically when the outer flow velocity is high [8,14]. As for DBD supplied by ac voltage, optimization of the electrode geometry or of the applied signal is expected to be a way to improve the performance of the nanosecond pulsed discharge [15,16]. Among these optimizations, the need for a large surface of plasma/fluid interaction is even more essential for plasma-assisted flow control implemented on aerodynamic model having realistic scale factor.…”
mentioning
confidence: 99%
“…Discharge filaments generate stronger compression waves with higher speeds than a diffuse discharge . In the experiments by Dawson and Little, negative polarity pulses produce a stronger compression wave for a given peak voltage and pulse energy than positive pulses . Wu et al found that as the pressure decreases from 760 Torr to 5 Torr, the discharge mode changes from a filamentary type to a glow type at around 80 Torr.…”
Section: Introductionmentioning
confidence: 99%
“…Moreau et al [7], for example, used a three-electrode configuration to increase the extension length up to the electrode gap, resulting in a 300% increase in the input energy from a current collected at the third electrode. Others [5,20,23] applied positive polarity pulses to investigate the effects of actuator parameters on the characteristics of gas heating generated in NS-DBD. Results from these studies suggested that dielectric thickness has little effect on flow control.…”
Section: Introductionmentioning
confidence: 99%